"My Stutter Has Put Me on the outside": Young South African Muslim Men Who Stutter Talk about Masculinities and Religion. (2nd January 2022) - Isaacs, Dane; Swartz, Leslie; Toefy, Yoesrie
Abstract: Presently, limited studies have explored how disabled Muslim men construct their masculinities. The present article examines how five young adult Muslim men in the Western Cape, who stutter, talk about their masculinities. A series of semi-interviews were conducted with these men. These semi-structured interviews were analyzed according to Edley's guide to discourse analysis. The findings showed that Islam played an instrumental role in men's discourses of masculinities. At the same time, participants indicated experiencing disablism as men who stutter, which resulted in them either resisting or reformulating dominant forms of masculinities. Implications for future research is discussed.